Extended approach to the lateral tibial plateau with central meniscal subluxation in fracture repair: feasibility and first clinical and radiographic results - Korthaus, Alexander (Eur J Trauma Emerg Surg, 2020)
PURPOSE: Anatomic reduction in tibial plateau fractures remains to be demanding. For further visualisation of and approach to the joint surface an extended lateral approach using a lateral femoral epicondyle osteotomy and subluxation of the lateral meniscus was recently described. First clinical and radiographic mid-term results of this technique are presented in this feasibility study. METHOD: Ten complex tibial plateau fractures treated with extended lateral approach and lateral meniscal subluxation were prospectively analysed. Clinical and radiographic results were objectified according to the Rasmussen scores. RESULTS: After a median follow-up of 8.6 (IQR 4.3) months good to excellent clinical and radiographic results were noted. The clinical Rasmussen Score showed a median of 25 (IQR 2.8) and radiographic a median of 17 (IQR 2.0) points. CONCLUSION: Good to excellent clinical and radiological scores were obtained after using an extended lateral approach with lateral femoral epicondyle osteotomy and central meniscus subluxation. No approach specific complications could be observed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00068-020-01467-1) contains supplementary material, which is available to authorized users.